The effects of a tailored postoperative delirium prevention intervention after coronary artery bypass graft: A randomized controlled trial - Mohammad Abbasinia; Atye Babaii; Zahra Nadali; Samaneh Pakzaban; Mohammad Abbasi; Mahdi Shamali (Tehran University of Medical Sciences, 2021)
Background & Aim: Delirium is a frequent complication in patients hospitalized in the intensive care unit following cardiac surgery. This study aimed to assess the effect of a tailored delirium preventive intervention on postoperative delirium and agitation reduction and length of intensive care unit stay in patients who underwent coronary artery bypass graft. Methods & Materials: In this single-blinded, single-center, randomized controlled design, 60 patients from a hospital in Qom, Iran, were randomly allocated to an intervention or a control group. In the control group, patients received routine care. In the intervention group, patients received routine care, a video tutorial, and the Hospital Elder Life Program. Outcomes were measured using the Confusion Assessment Method for the intensive care unit, Richmond Agitation-Sedation Scale, and length of intensive care unit stay in the second and third days after coronary artery bypass graft. Results: There were no significant differences in the rate of delirium episodes and mean scores of RASS between both groups in the second (P=0.301; P=0.125) and third days (P=0.389; P=0.057) after surgery, respectively. However, the mean duration of intensive care unit stays after surgery was significantly lower in the intervention group compared with the control group (P=0.042). Conclusion: This study indicated the tailored delirium prevention intervention could reduce the length of intensive care unit stay. However, the intervention did not reduce postoperative delirium episodes, nor did the intervention improve the RASS scores in the second and third days after coronary artery bypass graft. A future large multicenter trial with long-term follow-up is needed to assess further the effect of such an intervention.